FOSTERING STUDENTS’ LOGICAL THINKING ABILITY AS ONE OF THE 21ST CENTURY SKILLS THROUGH THE BLENDED LEARNING AIDED BY GOOGLE CLASSROOM - Henni Riyanti; Putri Dewi Nurhasana (Jurnal Fundadikdas (Fundamental Pendidikan Dasar), 2021)
The 21st Century skills are a challenge in the science and technology sector in addition to just being excelled in academic performance. Therefore, it is important to innovate the learning process of natural science into learning that refers to the development of 21st-century skills. Digital Age Literacy is one of the 21st Century skills, which requires the ability to have logical thinking ability as the core of digital-age literacy. Then, this study aimed to analyze the influence of natural science learning aided by google classroom media to fostering students’ logical thinking ability. This study was conducted by using a quasi-experimental study with a pretest-posttest non-equivalent control group design. Sampling was done using a simple random sampling technique. There were two classes in this study which had 77 participants consisting of 38 students as an experimental class and 39 students as a control class. The researcher collected the data of logical thinking ability using the instrument of logical thinking ability that has been tested for its validity and reliability. The analysis of data employed a t-test using SPSS 21. The results indicated that t-count > t-table (2.67 < 1.99) and p-value = 0.021 <0.05. It could be concluded that the natural science learning aided by google classroom media resulted in a significant influence on students' logical thinking ability. The result of the analysis could be used by educators for evaluating natural science learning, especially in elementary school in order to encourage the quality of students' logical thinking ability.